Technological and Economic Evaluation of Solid Waste Scavenging and Recycling Practices - Abd Malek, Zainul Dalila; Hassan, Mohd Nasir; Sapari, Nasiman (Universiti Putra Malaysia Press, 1996)
Existing solid waste scavenging and recycling practices in the Klang Valley, Malaysia were investigated through personal visits and field surveys to landfill sites, trading companies and factories involved in recycling. Collection of recyclable material has long been practised in landfill sites as it provides good additional income. Dealers of scrap and recyclable items who operate at the landfill sites provide a source of supply to manufacturing concerns. Glass recycling industries benefit greatly by using recycled cullet, which improves fuel efficiency. Major economic, technical and other constraints related to recycling are discussed.